Usability and acceptance of a mobile health wallet for pregnancy-related healthcare: A mixed methods study on stakeholders’ perceptions in central Madagascar - Lacroze, Etienne; Frühauf, Anna; Nordmann, Kim; Rampanjato, Zavaniarivo; Muller, Nadine; De Neve, Jan-Walter; Andriamampianina, Ralisimalala; Rajemison, Elsa; Bärnighausen, Till; Knauss, Samuel; Emmrich, Julius (PLOS ONE, 2023)
Background Several sub-Saharan African countries use digital financial services to improve health financing, especially for maternal and child health. In cooperation with the Malagasy Ministry of Health, the NGO Doctors for Madagascar is implementing a mobile health wallet for maternal health care in public-sector health facilities in Madagascar. Our aim was to explore the enabling and limiting factors related to the usability and acceptance of the Mobile Maternal Health Wallet (MMHW) intervention during its implementation. Methods We conducted a cross-sectional, mixed methods study with mothers and pregnant women and facility- (FBHWs) and community-based (CHWs) health workers from public-sector health facilities in three districts of the Analamanga region in Madagascar. We used a convergent design in collecting and analyzing quantitative and qualitative data. We performed one-stage proportional sampling of women who had signed up for the MMHW. All FBHWs and CHWs at primary care facilities in the intervention area were eligible to participate. Results and significance 314 women, 76 FBHWs, and 52 CHWs were included in the quantitative survey. Qualitative data were extracted from in-depth interviews with 12 women and 12 FBHWs and from six focus group discussions with 39 CHWSs. The MMHW intervention was accepted and used by health workers and women from different socioeconomic backgrounds. Main motivations for women to enroll in the intervention were the opportunity to save money for health (30.6%), electronic vouchers for antenatal ultrasound (30.2%), and bonus payments upon reaching a savings goal (27.9%). Main motivation for health workers was enabling pregnant women to save for health, thus encouraging facility-based deliveries (57.9%). Performance-based payments had low motivational value for health workers. Key facilitators were community sensitization, strong women-health worker relationship, decision making at the household level, and repetitive training on the use of the MMHW. Key barriers included limited phone ownership, low level of digital literacy, disinformation concerning the effects of the intervention, and technical problems like slow payout processes.